2004
DOI: 10.2298/abs0402053s
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrates and fishes in the part of the Danube flowing through the Iron Gate national park and possibilities of their protection under in situ and ex situ conditions

Abstract: Comparison of the results of later investigations of the Danube in the part flowing through in the Iron Gate (Đerdap) National Park with those of research conducted earlier (20 to 40 years ago) shows that changes have occurred in regard to the presence and especially the abundance of certain hydrobionts on this sector of the river, a finding that applies to all groups examined. The paper discusses the potential and results of conservation measures realized through both legal regulations and medium-term plans f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In potamon-type rivers in Serbia molluscs and oligochaetes are typically the most diverse and abundant groups. A similar community structure was observed by previous investigations of the Danube River in Serbia (Nedeljkovic 1979;Jakovcev 1987Jakovcev , 1988; Dju- kic & Karaman 1994; Arambasic 1994; Simic et al 1997;Martinovic-Vitanovic et al 1999;Simic & Simic 2004), as well as during the investigation of the Sava River (Paunovic 2004) and the Tisza River (Csanyi 2002).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In potamon-type rivers in Serbia molluscs and oligochaetes are typically the most diverse and abundant groups. A similar community structure was observed by previous investigations of the Danube River in Serbia (Nedeljkovic 1979;Jakovcev 1987Jakovcev , 1988; Dju- kic & Karaman 1994; Arambasic 1994; Simic et al 1997;Martinovic-Vitanovic et al 1999;Simic & Simic 2004), as well as during the investigation of the Sava River (Paunovic 2004) and the Tisza River (Csanyi 2002).…”
Section: Discussionsupporting
confidence: 85%
“…The Serbian reach of the Danube has been extensively examined since the early sixties (Liepolt 1967; Petrovic 1971Petrovic , 1973Petrovic , 1975Petrovic , 1978Jakovcev 1987Jakovcev , 1988Jankovic & Jovicic 1994;Martinovic-Vitanovic et al 1999;Simic et al 1997;Simic & Simic 2004;Paunovic et al 2005;Jakovcev-Todorovic et al 2005). The results of a 1986 study referring primarily to water pollution problems (Jankovic & Jovicic 1994) showed that water quality in the Serbian reach of the Danube deteriorated compared to the 1960-1970 period.…”
Section: Introductionmentioning
confidence: 99%
“…This is an area of considerable diversity of macroinvertebrates in comparison to the upper (Jakovcev 1987(Jakovcev , 1988Djukic & Karaman 1994), as well as downstream stretches (Djukic & Karaman 1994;Simic et al 1997;Simic & Simic 2004). The greater species richness of the transitional zone is mostly supported by its considerable habitat diversity in comparison to other sections, and is illustrated by the fact that Paunovic et al (2005) reported 84 aquatic macroinvertebrate taxa in a short stretch of the river section (between 1083 rkm and 1076 rkm).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that grass carp enhancement, along with the enhancement of silver, bighead and Prussian carp, exerted pressure on certain autochthonous species, especially the Danube carp (Simic and Simic 2004). Jankovic (1998) reported that aquatic-plant-based nutrition of grass carp resulted in a reduction in spawning areas for carp as a phytophilic species.…”
Section: Chinese Carpsmentioning
confidence: 99%
“…A study on the fish communities of the Danube River (Djerdap resevoir) during 1994, 1995 and 2000 revealed an increase in abundance of short-snouted pipefish in grassy litoral habitats (Simic and Simic 2004).…”
Section: Syngnathidaementioning
confidence: 99%